The mechanical stress-strain properties of single electrospun collagen type I nanofibers - Carlisle, Christine R. (Acta Biomater, 2010)
Knowledge of the mechanical properties of electrospun fibers is important for their successful application to tissue engineering, material composites, filtration and drug delivery. In particular, electrospun collagen has great potential for biomedical applications due to its biocompatibility and promotion of cell growth and adhesion. Using a combined atomic force/optical microscopy technique, we determined the single fiber mechanical properties of dry, electrospun collagen type I. The fibers were electrospun from a 80 mg/ml collagen solution in 1,1,1,3,3,3-hexafluro-2-propanol and collected on a striated surface suitable for lateral force manipulation by the AFM. The small strain modulus, calculated from three point bending analysis, was 2.82 GPa. The modulus showed significant softening as strain increased. The average extensibility of the fibers was 33% of their initial length and the average maximum stress (rupture stress) was 25 MPa. The fibers displayed significant energy loss and permanent deformations above 2% strain.